2010
DOI: 10.1002/jcb.22654
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of β‐catenin/Tcf signaling by flavonoids

Abstract: Functional activation of beta-catenin/T-cell factor (Tcf) signaling has been implicated in human carcinogenesis. We identified the inhibitory effect of various polyphenolic flavonoid compounds against beta-catenin/Tcf signaling in beta-catenin-activated cells. Genistein, kaempferol, isorhamnentin, and baicalein inhibited the transcriptional activity of beta-catenin/Tcf in HEK293 cells transiently transfected with a constitutively active mutant beta-catenin gene. To investigate the inhibitory mechanism, electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 32 publications
1
46
0
2
Order By: Relevance
“…Many factors have been identified as cotranscription factors in this signaling pathway. They are known to bind TCF-4 or b-catenin and function as transcription coactivators or inhibitors (27)(28)(29). In our previous study, we found that SPINDLIN1 interacts with TCF-4 and activates its activity (19), suggesting that SPINDLIN1 might promote cancer cell proliferation via this signaling pathway.…”
Section: Discussionmentioning
confidence: 90%
“…Many factors have been identified as cotranscription factors in this signaling pathway. They are known to bind TCF-4 or b-catenin and function as transcription coactivators or inhibitors (27)(28)(29). In our previous study, we found that SPINDLIN1 interacts with TCF-4 and activates its activity (19), suggesting that SPINDLIN1 might promote cancer cell proliferation via this signaling pathway.…”
Section: Discussionmentioning
confidence: 90%
“…As consequence Genistein inhibits prostate cancer (Li et al, 2008). Genistein also suppressed β-catenin/Tcf trancriptional activity in SW480 cells (colorectal carcinoma cells) in a dose-dependent manner (Park and Choi, 2010). Genistein affect the upstream components of the β-catenin/Tcf pathway by suppression of GSK-3β and Akt phosphorylation (Park and Choi, 2010).…”
Section: Targeting Wnt/β-catenin With Flavonoidsmentioning
confidence: 97%
“…Kaempferol suppressed β-catenin/TCF transcriptional activity in SW480 colon cancer cells, which has inactivating mutation of the APC gene and shows a constitutively active transcriptional activity of β-catenin/TCF. This can further suppress c-Myc and cyclin D1 (Park & Choi, 2010). Naringin also has shown to target β-catenin in breast cancer cells (Li et al, 2013).…”
Section: Fig 4 -Effect Of Methanol Extract Of Amla Seed (As) or Pulpmentioning
confidence: 97%